2003
DOI: 10.1177/089686080302300509
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus Aureus Prophylaxis and Trends in Gram-Negative Infections in Peritoneal Dialysis Patients

Abstract: Objective To examine gram-negative exit-site infection and peritonitis rates before and after the implementation of Staphylococcus aureus prophylaxis in peritoneal dialysis (PD) patients. Design Prospective data collection with periodic implementation of protocols to decrease infection rates in two PD programs. Patients 663 incident patients on PD. Interventions Implementation of S. aureus prophylaxis, beginning in 1990. Main Outcome Measures Rates of S. aureus, gram-negative, and Pseudomonas aeruginosa exit-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 15 publications
1
56
0
1
Order By: Relevance
“…Similar findings were also observed by Banskar et al [19]. Two bacterial genera, Staphylococcus and Streptococcus, may cause pneumonia, meningitis, bacteremia, infectious lesions, neonatal infections, and septicemia [73,74]. We observed that the R. monceros gut microbiome also harbors known pathogenic microbes, but their pathogenicity has not been determined.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were also observed by Banskar et al [19]. Two bacterial genera, Staphylococcus and Streptococcus, may cause pneumonia, meningitis, bacteremia, infectious lesions, neonatal infections, and septicemia [73,74]. We observed that the R. monceros gut microbiome also harbors known pathogenic microbes, but their pathogenicity has not been determined.…”
Section: Discussionsupporting
confidence: 90%
“…9,10,19 Recently, some authors found a shift from Gram-positive to an increased incidence of Gram-negative peritonitis episodes. 2,5,14 Piraino et al . showed that the decrease in S. aureus peritonitis and catheter infections was striking after the start of prophylaxis in 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported that infections due to Gram-negative bacilli trended gradually downward from 1983 to 1988, and fell slightly but insignificantly from 1988 to 1989 to subsequent years. 5 APD has less effect on children's education and lifestyle, and has been therefore the preferred peritoneal dialysis modality, especially in infants and young children. APD use has increased in recent years, perhaps this has caused the relative increase in Gram-negative peritonitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of mupirocin prophylaxis for catheter infections there has been a decline in Gram‐positive bacterial peritonitis; however, the incidence of Gram‐negative, polymicrobial and fungal peritonitis remained stable (10). The special case of “enteric peritonitis”, also called abdominal catastrophe, deserves a special focus, since its only known and non‐modifiable risk factor is old age; it is characterized by high mortality (up to 46%) and demands surgical exploration, correction of the abdominal pathology and, almost always, peritoneal catheter removal (4).…”
mentioning
confidence: 99%